Homogenous, or Heterogenous? A Comparative Analysis of Three Czech Journalists Generations - Václav Moravec; Marína Urbániková; Jaromír Volek (Communication Today, 2025)
The goal of this article is to explore the degree of homogeneity among three generations of Czech journalists working (or intending to work) in the Czech media. We have defined three generations as follows: pretransitive, transitive and post-transitive. Using a secondary analysis of data from two independent studies, which focused on describing professional attitudes of Czech journalists and journalism students, we are trying to ascertain the existence of the so-called “generational effect”. Quantitative analysis including cluster analysis indicates no major attitudinal differences between all compared generations, in spite of radical socio-political and media system changes after 1989. In general, the comparison of the selected attributes shows striking homogeneity in all three journalistic generations that especially share their professional and political values. The key to a weak differentiation between the generations in question is their distinctive similarity in their acceptance of liberal right-wing ideology and high socio-economic capital, which interconnects all hypothetically constructed professional groups. There are also some partial differences, especially the low level acceptance of the predominance of market logic by the youngest post-transitional generation in the news media.